2003
DOI: 10.1161/01.cir.0000087481.55887.c9
|View full text |Cite
|
Sign up to set email alerts
|

From Vulnerable Plaque to Vulnerable Patient

Abstract: Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
308
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,505 publications
(326 citation statements)
references
References 73 publications
4
308
0
3
Order By: Relevance
“…TRFs have well‐known limitations for accurate assessment of individual cardiovascular risk 1, 31. It is crucial to identify biomarkers that may improve the identification of subjects at risk and guide preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TRFs have well‐known limitations for accurate assessment of individual cardiovascular risk 1, 31. It is crucial to identify biomarkers that may improve the identification of subjects at risk and guide preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For plaque area, the risk estimates in our study were stronger in women than in men, suggesting that assessment of carotid plaque may be a more important tool in risk classification of women than in men. It is suggested that <10% of the population who test positive for atherosclerosis will experience a near‐term event 1. Identification of reliable imaging and serological markers of disease activity is therefore essential to improve the selection of vulnerable patients and cost‐effectiveness of screening with carotid ultrasound in the primary prevention setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations